In-depth analysis and implementation strategies of 3D graphics technology for VR animation production - Kim, Dong-Jo; Kim, Ji-Young (Edelweiss Applied Science and Technology, 2025)
The application of 3D graphics technology has garnered significant attention for its transformative impact across various industries, particularly in virtual reality (VR) animation production. This study investigates the role of 3D graphics in enhancing VR animation by examining its contributions to interactive storytelling, user engagement, and production efficiency. Adopting a qualitative analytical approach, this research explores key technological advancements in VR animation, including real-time rendering, photorealistic modeling, and the integration of Building Information Modeling (BIM) and augmented reality (AR) software. The findings indicate that 3D graphics technology substantially improves the realism and interactivity of virtual environments, facilitating seamless content creation across domains such as film, gaming, and architectural visualization. However, several challenges persist, including performance optimization, user experience refinement, and accessibility considerations, which must be addressed to ensure broader adoption and usability. In conclusion, while the integration of 3D graphics and VR animation presents significant opportunities for artistic and commercial applications, overcoming technological limitations remains crucial for the field’s continued advancement. The practical implications suggest that industry professionals should adopt innovative strategies, such as AI-driven automation and globally networked collaboration, to optimize production workflows and improve the accessibility of VR experiences. Future research should focus on refining technological frameworks and best practices to support the sustainable evolution of VR animation and 3D graphics development.